Trials and Tribulations ‐ an RCT comparing manualized family therapy with Treatment as Usual and reflections on key issues that arose in the implementation. Issue 2 (6th April 2016) - Boston, Paula; Cottrell, David
Abstract : SHIFT has been one of the largest RCTs in the field of systemic family therapy in the UK. The study took place over five years, including three major centres with fifteen Trusts and twenty‐five family therapists who worked with a manualized treatment in CAMHS with adolescents who self‐harmed. While the results are not available at the time of this publication, this paper will briefly describe the pre‐ existing factors which were helpful in developing a successful bid, clinical and managerial elements of 'real world research' of complex psychological processes and the construction of the manualized systemic family therapy. It also offers examples of some of the unanticipated events in the life of such a large trial. Practitioner Points: Large trials develop from small studies and clinicians are urged to look for opportunities for research partnerships Investment in time for consideration of difficult issues as they arise is essential for effective trial management The balance between research rigour and 'real life' practice is an inevitable area of tension and requires consideration of both immediate and outcome consequences